(untitled) (Gaceta Técnica, 2019)
Barquisimeto, capital of Lara State, Venezuela, has a Local Urban Development Plan approved in August 2003 whose validity was estimated until 2016, which is why the municipal authorities have the responsibility of assuming its updating or the formulation of a new plan that rules the urban planning of the city for the next twenty years. The formulation of the plan is a task in which all the dimensions that make up the development of the city must be considered given the essential multi-sectorial approach, requiring solving some problems in the urban dynamics, as well as some weaknesses of the current instrument. Through this work we propose a set of ideas on key aspects that the new instrument should address, such as: consider international agreements related to the objectives of sustainable development and the new urban agenda, the role of Barquisimeto in the sub-region, the integration of neighborhood areas, the incorporation of Transbarca, the consideration of new employment centers and dynamics, review of zoning, innovation in the provision of equipment and the protection of built heritage, incorporating urban action programs from the perspective of the strategic plans and, finally, the strategy of implementing the macro plan with micro plans. To achieve its purpose, the work identifies information sources and local, national and international experiences that will serve as a reference to the professional team that assumes the challenge of designing the new Local Urban Development Plan